Potensi Estrak Daun Miana (Coleus atropurpureus) Menghambat Pertumbuhan Malassezia furfur pada Penderita Pityriasis versicolor - Anita Rahmawati; Effendy Rasiyanto (Halu Oleo University, 2019)
ABSTRACTBackground: Pitryasis versicolor is one of the fungal infections of the skin caused by the fungusMalassezia furfur often infecting residents in tropical climates due to the temperature and humidity suitable for the growth of the fungus, so an alternative drug is needed such as herbs such as miana leaves which contain plants flavonoids, saponins, steroids, tannins, essential oils, eugenol, polyphenol compounds, alkaloids, ethyl salicylates, calcium oxalate, and rosmarinic acid (RA) compounds.Pusrpose: The purpose of this study was to determine the antifungal potential of miana leaf extract against Malassezia furfur fungi isolated from patients with Pitryasis versicolor (Panu). Method: This type of research is a laboratory experiment with the paper disk method. Result: The research results obtained from the inhibitory test were Miana leaf extract with a concentration of 250 mg / ml, 125 mg / ml, 62.5 mg / ml, 31.25 mg / ml, and 15.625 mg/ ml, with the diameter of each inhibition zone 0.00 mm. Conclusion: From the results of the study it can be concluded that miana leaf extract does not have the potential to inhibit the growth of Malassezia furfur fungus due to Tinea versicolor.Keywords: inhibition test, Malassezia furfur, Pitryasis versicolor